Hydatid Disease: Current Status Of Chemotherapy And Drug Delivery Systems - Elissondo, María Celina (2013)
Human echinococcosis or hydatid disease still causes serious health problems with a worldwide geographical distribution. This parasitic infection is a chronic, complex, and still neglected disease. Currently four treatment modalities are in use: surgery, PAIR (puncture, aspiration, injection of protoscolicidal agent, reaspiration), chemotherapy and a “watch and wait” approach for inactive, clinically silent cysts. Over the past 30 years, chemotherapy with benzimidazoles (BZ), like albendazole and mebendazole, has been used increasingly to treat this pathology. Unfortunately, 20%–40% of the cases do not respond favorably to such chemotherapy and these drugs produce stabilization, rather than cure in the majority of patients. However, the overall efficacy of BZ has been overstated in the past. With regard to these difficulties, novel therapeutical tools are needed to optimize treatment of human echinococcosis. On the one hand, a number of compounds have been investigated, either using in vitro cultured parasites and/or applying to in vivo rodent models. Tested compounds include BZ derivatives such as flubendazole, and oxfendazole, as well as other anti-infective agents like ivermectin, nitazoxanide, genistein, artemisinin, timol, rapamycin, and anti-cancer agents such as 2-methoxyestradiol and cyclosporine A. Although some of these compounds showed promising activities in vitro, and also in the rodent models, they have not been yet translated to clinical applications. On the other hand, different drug delivery systems have been developed in order to improve the efficacy of several active pharmaceutical ingredients (APIs) such as oil in water emulsion, liposomes and nanoparticles among others. The present review article summarizes the chemotherapeutic state-of-the-art and the research done in the field of drug delivery systems regarded human echinococcosis.